Sistem Pengaman Sepeda Motor Dengan Arduino Berbasis Android - Zulfian Wathoni; Khairunazri; Muh. Fahrurrozi (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2020)
Motorcycle security systems today still use manual locks that are easily damaged by thieves in seconds. Although there are several motorbike manufacturers that have used Shutter Key Magnets, in fact, this security is not efficient for security because it is prone to damage using only the T key. In this digital era, many new security systems are safer than manual locks. Therefore, the idea of ​​designing This tool the author uses Ar-duinoUno and Smartphone as controllers in starting a motorcycle easily. For example a computer-based security system.